2017
DOI: 10.1080/10401334.2016.1274262
|View full text |Cite
|
Sign up to set email alerts
|

Who Is the Preferred Tutor in Clinical Skills Training: Physicians, Nurses, or Peers?

Abstract: Kruskal Wallis analysis was used to compare students' scores for their tutors. The students' satisfaction with tutors was high for all of the tutors. However, there was no difference between students' scores in suturing skill, and between physician, nurse, and peer tutors' coaching skills. Insights: In this study, we revealed that physician, nurse, and peer tutors were equally effective on the students' performances. They were also regarded as effective in their teaching role by students. But the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…5 The role of tutors is found to be equivalent to clinicians and nurses in clinical skills training. 6 Peer tutoring nurtures development of metacognitive, communication and professionalism skills among the peer tutors. 7 They relieve the burden of teaching from the faculty thereby, enabling them to take part in productive activities.…”
mentioning
confidence: 99%
“…5 The role of tutors is found to be equivalent to clinicians and nurses in clinical skills training. 6 Peer tutoring nurtures development of metacognitive, communication and professionalism skills among the peer tutors. 7 They relieve the burden of teaching from the faculty thereby, enabling them to take part in productive activities.…”
mentioning
confidence: 99%
“…The PAL method is a viable alternative to classic teaching methods. Whether PAL is applicable for amending and improving medical training is the subject of many studies [8,14,[23][24][25]. When comparing the PAL concept with average faculty medical teaching, no difference in knowledge and skill gain could be shown [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Peer-assisted learning (PAL) is an increasingly popular strategy for supporting teaching staff at universities with respect to the growing demand for medical knowledge to be taught among medical students [11,12]. The PAL concept, based on technically and didactically trained student tutors, has proven to be an attractive and feasible extension as well as an effective alternative to common medical teaching [13,14]. In Germany, this concept has been successfully established throughout different skills labs and has been shown to be an effective and viable teaching technique [15].…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 However, 1 study that did look at clinical skills found that tutee satisfaction was similar when taught by peer tutors or faculty, but results were gathered after a single session, rather than after a long-term program of weekly sessions as assessed in our study. 25 …”
Section: Discussionmentioning
confidence: 99%